French military masculinities and the birth of cinéma colonial: triangulating queer desire in Jacques Feyder's L'Atlantide (1921). (2nd October 2021) - Nevin, Barry
ABSTRACT: Jacques Feyder's L'Atlantide (1921) is widely considered not only cinéma colonial 's first major representative example but also one of the genre's most emblematic narratives. However, ambiguities in the film's portrayal of the mission civilisatrice have received comparatively little analysis. This article aims to expand on our understanding of L'Atlantide and the mirror it held up to interwar France in three main stages. First, it situates the film's discourses of gender and colonialism within present post-colonial scholarship. Second, it analyses the aesthetic and political contexts of L'Atlantide, paying particular attention to how the film offered a remedy to France's ailing postwar film industry and, albeit superficially, discovered a way to address a country undergoing a crisis of masculinity. Third, through a discussion of the sexually ambiguous relationships that structure the narrative's central erotic triangle, this analysis posits that Feyder's film registered France's postwar trauma and the fallibility of French colonial rule. This article ultimately argues that although L'Atlantide played a foundational role in perpetuating certain monolithic stereotypes, it also established a subversive tradition in cinéma colonial which would flourish during the interwar period in films such as Julien Duvivier's Pépé le Moko (1937) and Jean Grémillon's Gueule d'amour (1937).